APLIKASI PEMBELAJARAN ANATOMI RANGKA DAN SISTEM PENCERNAAN MANUSIA BERBASIS ANDROID (Information Technology and Telematics, 2015)
Abstract - Many problems that arise in the process of learning biology in schools due to the biology lesson taught to memorize, one of the sub topics that often become rote is about anatomy order and the human digestive system. The problems regarding the lack of understanding, interest and student learning outcomes can not be separated from the way teachers teach. This is due to the large number of subjects to be taught while the limited time available so that teachers tend to give material without trying to arouse interest in student learning. Learning Application Framework Anatomy and Human Digestive System Based Android will help high school students in particular classes XI and biology teachers to increase student interest in the course from the framework and the human digestive system. In this study, the Android SDK as Android application developers who use the Java programming language. Which will be installed on the mobile and Eclipse ADT Bundle as a media creation of applications.   Keywords: Android, Anatomy, Learning   Abstrak - Banyaknya permasalahan yang timbul dalam proses pembelajaran biologi di sekolah-sekolah disebabkan karena matapelajaran biologi diajarkan untuk dihafal, salah satu sub bahasan yang sering menjadi hafalan yaitu tentang anatomi rangka dan sistem pencernaan manusia. Permasalahn mengenai rendahnya pemahaman, minat dan hasil belajar siswa tidak terlepas dari cara mengajar guru. Hal ini disebabkan banyaknya jumlah pokok bahasan yang harus diajarkan sedangkan waktu yang tersedia terbatas sehingga guru cenderung memberikan materi saja tanpa berusaha membangkitkan minat belajar siswa. Aplikasi Pembelajaran Anatomi Rangka dan Sistem Pencernaan Manusia Berbasis Android akan membantu siswa SMA khsusnya kelas XI dan guru biologi untuk meningkatkan minat belajar siswa dalam matapelajaran rangka dan sistem pencernaan manusia. Dalam penelitian ini Android SDK sebagai pengembang aplikasi Android yang menggunakan bahasa pemrograman Java. Yang akan dipasang pada mobile dan Eclipse ADT Bundle sebagai media pembuatan aplikasi. Kata Kunci : Android, Anatomi, Pembelajaran